Penerapan Akuntansi Pertanggung Jawaban dalam Penilaian Kinerja Pusat Pendapatan pada PT Jujur Jaya Sakti Makassar - Rosida Maedina Agus (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
The purpose of this study was  whether Honestly Jaya Sakti PT Makassar has implemented accounting in assessing the performance of the central revenue. This type of research is a descriptive study, the type of data used are primary data and secondary data, engineering data collection is done with Interview Techniques and Technical Documentation, Data Analysis method is the descriptive method as well as the location and Research Schedule housed in PT Honestly Jaya Sakti Makassar carried out for two months. Results of the study indicate that the honest Jaya Sakti PT Makassar has applied the accounting but not fully. Implementation of accounting systems by the company can be seen from the budget which has involved all parts of both subordinates and superiors as well as the use of the budget as a performance assessment tool center managers accountable. Meanwhile, if viewed from the organizational structure, the company has established the delegation of authority and responsibility to each part of the organization but not yet good enough. It is manifested in the presence of a manager who has the duty and responsibility of the head of the branch, namely double Honestly Jaya Sakti PT Makassar which also serves as a sales manager.